EDUKASI SEKS BERBASIS INTEGRASI AGAMA DAN SAINS - Saeful Bahri; Lana Laelatussyifa (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This research will answer important questions about the sex education model based on the integration of religion and science applied at MTs Mathla'ul Anwar Sugihwaras Pemalang. According to the focus of the problem studied, this study uses a qualitative approach in the form of field research. The data was collected using interviews, observations and documentation, while the analysis techniques were taken using descriptive methods. The results of the research show that, (1) sex education is carried out by teachers in the field of study through the learning process by combining materials related to sex in the PAI (represented by fiqih and akidah akhlak) with scientific findings (IPA and PJOK), (2) using the team teaching method by several teachers to develop sex education that is integrated interdisciplinary, (3) the need for integral sex education modules/textbooks based on religious and science subjects (general), with the addition of sub-sub-topics from various other literacy.